TRANSFORMATION OF THE FINANCIAL AND BANKING SYSTEM IN THE DIGITAL ECONOMY - Samatov Khurshid; Jabbarov Abdulla (Ecomind Press, 2025)
This article examines the level of development of the financial and banking system in the context of the digital economy, its transformation, and future prospects. The introduction of digital technologies in the banking sector, the importance of electronic payment systems, and modern forms of financial services are analyzed. Additionally, directions for ensuring financial stability in the context of the digital economy are presented.
Keywords: Digital economy, financial and banking system, electronic banking services, fintech, blockchain, digital payments, transformation, online banking system.